Factors affecting the Audit expectation gap – A case study in Vietnam - Hoai, Nguyen Thu (Edelweiss Applied Science and Technology, 2024)
The concept of the audit expectation gap (AEG) is not novel in the field of auditing, having first been introduced approximately 50 years ago in Liggio's [1] study. Since then, AEG has garnered significant attention from both practitioners and academic researchers. However, there remains ongoing debate regarding the methods used to measure AEG and the factors that influence it. This study aims to address these gaps by proposing a new approach for measuring AEG and presenting a research model to identify the factors that impact AEG. Additionally, the study provides empirical evidence from Vietnam to validate the proposed measurement method and research model. The findings indicate the presence of AEG in Vietnam and highlight that factor such as users' understanding of audit, users' neess from audit, auditor’s independence, auditor’s competence, and the insufficient audit standards significantly influence AEG within the Vietnamese context.